Edgardo Navarro, A chimerical painter - Guiot, Nathalie (Cinzontle, 2019)
«When you look at the roofs of Paris, you just see grey tiles, while I see the skin of a serpent, that of Quetzalcoatl (a feathered serpent), my culture…» so the painter Edgardo Navarro confides to me in his studio in Paris. Architecture is one of the sources of inspiration for this young painter originating from Mexico, but who’s been living in France for some years now. He grew up with muralists like Orozco, Siqueiros and Rivera … all of them artists who coloured his history books. «Those men have made the revolution. The idea of art for art’s sake belongs to modernity. However, to Mexican muralists and many artists of East Germany art is rather a vehicle to exclaim their political values. » When he arrived in France in the 2000’s, Edgardo Navarro first studied at La Villa Arson, where he tried his hand at the language of the conceptual. Afterwards, he went on to study at Leipzig where he plunged into the architectural context of East Germany and he formed himself together with Neo Rauch. At this city charged with history, he learned about the rigid construction of space and abandoned all political fancy. Ever since his return to Paris, where he still lives and works, Edgardo has to cross the entire capital every single day from North to South to get to his studio, which offers a fantastic view over the roofs of Paris.